Managing a Complex Global Circular Economy Business Model: Opportunities and Challenges. (May 2018) - Hopkinson, Peter; Zils, Markus; Hawkins, Philip; Roper, Stuart
This article presents an in-depth case study detailing the history, experiences, and wider practitioner and policy lessons from a circular economy business model over a 30-year period, highlighting the successes, difficulties, and conflicts of adopting a circular economy model. The case is based on interviews, key documents, and customer insight. The findings demonstrate how sustained circular economy business practices can deliver significant new revenues, resource productivity, and business continuity benefits, but also require managers and practitioners to develop competencies and capabilities, such as balancing linear and circular systems, to address complex and highly dynamic factors, including rapid technological shifts and market volatility.